Nutritional Status and Body Composition of Independently Living Older Adults in a Snowy Region of Japan. (28th April 2017) - Shimoda, Tomoko; Suzuki, Teppei; Takahashi, Noriko; Tsutsumi, Kaori; Samukawa, Mina; Yoshimachi, Shoko; Goto, Teruaki; Enomoto, Hisashi; Kise, Nobuyuki; Ogasawara, Katsuhiko; Yoshimura, Sadako
Lifestyle diseases, which are associated with nutrition, account for 30% of elderly requiring long-term care. To increase health expectancy among Japan's rapidly aging population, we investigated the nutritional status and body composition of elderly adults living in a region subject to heavy snowfall, to identify pertinent health indicators. The dietary habits of 288 local residents aged ≥50 years were analyzed using body composition and a brief-type self-administered diet history questionnaire. Body mass index of all residents was normal. Basal metabolic rate (BMR) and muscle mass were reduced in the older group. Dietary habits did not differ with age among men, but older women had significantly higher dietary intake. BMR and muscle mass declined with age, even when dietary intake was sustained. Despite sufficient dietary intake, independently living older adults demonstrate less efficient use of food with age. Interventions to reduce excessive sodium and protein intake are required.